Graphene oxide: an effective acid catalyst for the synthesis of polyoxymethylene dimethyl ethers from methanol and trioxymethylene. Issue 4 (22nd January 2016) - Wang, Ruiyi; Wu, Zhiwei; Qin, Zhangfeng; Chen, Chengmeng; Zhu, Huaqing; Wu, Jianbing; Chen, Gang; Fan, Weibin; Wang, Jianguo
Abstract : Graphene oxide as an acid carbocatalyst performs excellently in the synthesis of polyoxymethylene dimethyl ethers from methanol and trioxymethylene. Abstract : Graphene oxide (GO) prepared by a modified Hummers' method exhibits excellent catalytic performance in the synthesis of polyoxymethylene dimethyl ethers (PODE n ) from methanol (MeOH) and trioxymethylene (TOM), owing to a synergy between the sulfonic groups and the hydroxyl and carboxyl groups present on the surface of GO with a unique layered structure.